The poetry of war - Winn, James Anderson, 1947-2019. (Cambridge ; New York : Cambridge University Press, 2008)
Poets from Homer to Bruce Springsteen have given voice to the intensity, horror, and beauty of war. The greatest war poets praise the victor while mourning the victim; they honor the dead while raising deep questions about the meaning of honor. Poets have given memorable expression to the personal motives that send men forth to fight: idealism, shame, comradeship, revenge. They have also helped shape the larger ideas that nations and cultures invoke as incentives for warfare: patriotism, religion, empire, chivalry, freedom. The Poetry of War shows how poets have shaped and questioned our basic ideas about warfare. Reading great poetry, the author argues, can help us make informed political judgments about current wars. From the poems he discusses, readers will learn how soldiers in past wars felt about their experiences, and why poets in many periods and cultures have embraced war as a grand and challenging subject.
Introduction: Terrible beauty -- Honor and memory --Shame and slaughter -- The cost of empire -- The myth of chivalry -- Comrades in arms -- The cause of liberty.
Includes bibliographical references (p. 220-233) and index.
Keywords: War poetry -- History and criticism; Poetry -- History and criticism; War in literature